Recovery of Focal Brain Ischemia-Induced Behavioral Dysfunction by Intracerebroventricular Injection of Microglia - Yoshihisa Kitamura; Daijiro Yanagisawa; Masatoshi Inden; Kazuyuki Takata; Daiju Tsuchiya; Toshiyuki Kawasaki; Takashi Taniguchi; Shun Shimohama (Elsevier, 2005)
The function of microglia in the brain parenchyma is not fully understood. Occlusion of the middle cerebral artery (MCA) and reperfusion caused behavioral dysfunction with massive neuronal loss in the rat cerebral cortex and striatum. When exogenous microglia were microinjected into the intracerebroventricle (i.c.v.) during MCA occlusion, focal ischemia-induced behavioral dysfunction was significantly inhibited. At that time, many microglia migrated into the ischemic lesion, and microglia-derived neuron-like cells were barely detectable. These results suggest that exogenous microglia protect against focal ischemia-induced neurodegeneration and improve behavioral dysfunction. Keywords:: behavioral recovery, microglia, focal brain ischemia